THE EFFECT OF CUSTOMER RATING, CUSTOMER REVIEW AND CASH ON DELIVERY PAYMENT METHOD ON THE PURCHASE DECISION OF JASMINE JILBAB PRODUCTS IN THE SHOPEE MARKETPLACE - Damayanti, Vina; Ekasari, Ratna (Universitas Maarif Hasyim Latif, 2025)
This study aims to determine the Influence of Customer Rating, Customer Review and Cash On Delivery Payment Method on Purchase Decisions for Jasmine Jilbab Products in the Shopee Marketplace. This study is a quantitative study with a data collection technique using a questionnaire. The sample consisted of 100 respondents. The sampling technique used was purposive sampling with the criteria that respondents were customers of jasmine jilbab products in Sidoarjo who had made purchases at the Shopee Marketplace. Primary data management was carried out using the Statistic Package for Social Science (SPSS) analysis technique with multiple regression analysis methods. The results of this study indicate that Customer Rating, Customer Review and Cash on Delivery Payment Method have a Positive and Significant Effect on Purchase Decisions for Jasmine Jilbab Products in the Shopee Marketplace.